PENGARUH KUALITAS PRODUK DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA TOKO 3 SECOND DISTRO KOTA BENGKULU - Haryanto, Andesva Rafles; Ekowati, Sri (Yayasan Insani Mandiri Santani, 2023)
This study aims to determine the effect of product quality and sales promotion on product purchase decisions at the 3 Second Distro Store in Bengkulu City. This type of research is a type of quantitative descriptive research, the object of this research is the consumer of Toko 3 Second Distro which is precisely located on Jl. Putri Gading Cempaka, Gading Cempaka District, Decrease Village, Bengkulu City, Bengkulu. The sampling method uses a non-probabilty technique, namely accidental sampling. The number of respondents in this study were 160 people. Methods of data collection using a questionnaire. The data analysis technique is using Multiple Linear Regression Analysis Test, and Hypothesis Testing, namely t-test and f-test. The results of this study can be concluded that the variable Product Quality 3 Second Distro has a positive effect on Purchase Decisions, Sales Promotion has a positive effect on Purchase Decisions, and Product Quality and Sales Promotion together have a positive and significant effect on Product Purchase Decisions at 3 Second Distro Stores. Bengkulu City. Keywords: Product Quality, Sales Promotion, Purchase Decision